(untitled) (South East Asia Journal of Public Health, 2016)
Poverty, large population, socio- economic inequalities and inadequate access to proper health care facilities are the key causes of under nutrition in Bangladesh. Adolescents are the most vulnerable group for under nutrition and having great consequence as they will be parent in future. Studies on nutritional status of adolescent girls are fewer in number and have great effect for intervention. The objective of this study was to assess the nutritional status and predisposing factors of under nutrition among the adolescent girls in Bangladesh. A community-based cross-sectional survey was carried out from July to December 2013. Adolescent girls were the study population. Data was collected by face to face interview at household level. According to BMI category (kg/m2) the prevalence of under-weight (BMI<18.5) was found 65.9% and as per Gomez Classification (Weight for age), the prevalence of malnutrition was 48.2% (mild), 23.5% (moderate) and 2.8% (severe) categories and finally, as per Water Low Classification wasting found 16.6% (mild), 3.5%(moderate) and 0.2% severe categories. On the other hand, stunting found 39.6 % (mild), 9.2% (moderate) and 2.3% (severe) categories. Prevalence of under nutrition was found much higher (82.3%) among younger age group (?12 years). Higher prevalence of under-nutrition also found among the functionally illiterate adolescent girls, it was 75.8% and 51.3% among illiterate and literate group respectively. In both of the cases difference was statistically significant (p<0.001). The prevalence of illness found higher among under-weight adolescent girls in last two weeks compare to healthy adolescent girls both in rural and urban settings. This difference also found statistically significant (p<0.001). Under nourishment found higher among younger and low literate girls. Prevalence of other symptoms is also found higher among them. South East Asia Journal of Public Health Vol.6(1) 2016: 3-7